Perlaksanaan dan Cabaran Teknologi Internet of Things (IoT) Di Kalangan Kontraktor Dalam Sektor Industri Pembinaan - Mohd Jaini , Mohammad Fahrulnazmi; Yahya, Mohd Yamani (Research in Management of Technology and Business, 2021)
The Internet of Things, or ‘IoT,’ is one of the most prominent themes in the 4.0 industrial revolution, and it is projected to have a significant impact on the country’s diverse industrial sectors. The Internet of Things (IoT) is a network of physical items, cars, and other things that are equipped with electronics, software, sensors, actuators, and network connections to collect and share data. The Malaysian economy will encounter difficulties in the current period of industrial revolution 4.0 if the industry is not ready. The objectives of this paper is to determine the extent to which IoT technology is being used by contractors in the construction sector, as well as the sorts of IoT applications that are being employed. The focus of this research is on G7 rated contractors in Johor Bahru. The questionnaire was delivered in the form of a Google form, and the study methodology was quantitative. According to the findings of the study, the use of websites as a source of reference to collect data, the internet as a medium to advertise tenders, and the use of drones to monitor work on construction sites are among the most common IoT technology implementations among the highest contractors. Email, social media platforms like WhatsApp, Facebook, and Telegram, and GPRS applications like Waze and Google Maps are all used by contractors in the construction sector. Finally, to enhance the use of IoT applications in the construction industry, the installation and encouragement of these applications should be sustained.